Gut firmicutes: Relationship with dietary fiber and role in host homeostasis - Sun, Yonggan; Zhang, Shanshan; Nie, Qixing; He, Huijun; Tan, Huizi; Geng, Fang; Ji, Haihua; Hu, Jielun; Nie, Shaoping (Critical reviews in food science and nutrition, 2023)
Firmicutes and Bacteroidetes are the predominant bacterial phyla colonizing the healthy human gut. Accumulating evidence suggests that dietary fiber plays a crucial role in host health, yet most studies have focused on how the dietary fiber affects health through gut Bacteroides. More recently, gut Firmicutes have been found to possess many genes responsible for fermenting dietary fiber, and could also interact with the intestinal mucosa and thereby contribute to homeostasis. Consequently, the relationship between dietary fiber and Firmicutes is of interest, as well as the role of Firmicutes in host health. In this review, we summarize the current knowledge regarding the molecular mechanism of dietary fiber degradation by gut Firmicutes and explain the communication pathway of the dietary fiber-Firmicutes-host axis, and the beneficial effects of dietary fiber-induced Firmicutes and their metabolites on health. A better understanding of the dialogue sustained by the dietary fiber-Firmicutes axis and the host could provide new insights into probiotic therapy and novel dietary interventions aimed at increasing the abundance of Firmicutes (such as Faecalibacterium, Lactobacillus, and Roseburia) to promote health.